Variation of water quality along the kaluganga - Welikala, D.N.P. (My University, 2010)
Comparativestudy on variation of water quality along the Kalu Ganga with the Sri Lanka standardof potablewater (614:1983)wasthe main aim ofthis researchI. Identifyingthe suitable areasofKaluGanga water for drinking purposes, introducebaseline water quality parametersfor Ganga,investigatethe intrusion of hazardous chemicals to Ganga and develop a water quality indexfor Ganga were other achievements. In here,the physical and the chemical requirement of Sri Lanka standard of potable water was considered.Further, thirty six separate water samples were analyzed along the Kalu Ganga in Ratnapuara,Haraniyawaka,Ellagawa, Kandana, Kethhena and Kalutara once a month from June 2009to November 2009 continuously. The selected physical parameters were colour and turbidityand chemical parameters (basic) were pH, electrical conductivity, chloride (as Cl), nitrate(as N), nitrite (as N), phosphates (as PO4) and iron (as Fe). The selected chemical parameters(optional) were copper (as Cu), manganese (as Mn), zinc (as Zn) and chemical oxygendemand (COD). Further cadmium (as Cd), lead (as Pb) and chromium (as Cr) were measuredas toxic substances under chemical parameters. The parameter biological oxygen demand(BOD) was also measured. Thestudyrevealed that there was no location found containing water in excellent condition but mostof the parameter results compliedwiththe Sri Lanka standard of potable water (614: 1983) andsome varied. The variations depend basically on tributaries which are connected to Kalu Ganga,the rain fall, sand and gem mining process and tidal variations. Based on the study defineda Water Quality Index (WQI) as a single numeric score that describes the surface water qualityconditionat a particular time and a location. It was found that the water quality in Kalu Gangadecreasegraduallyfromupperstreamto downstreamfromgoodto fair.Dependingofthe locationdifferentparameters were responsible for the water quality index variation such as high colour,high turbidity, low pH, high chemical oxygen demand, higher levels of iron, manganese andcadmium.Special attention has to be given to the area of Kandana because the water quality indexchangedfrom usual pattern and was found to be 75.5. Due to the importance of Kalu Ganga water body, such studies are required to identify the changesin water quality in advance and it would help to take precautions in future problems.